The importance of psychological adjustment among school students (theoretical study) - Al-Brihi, Ra'id Muhsen Qasim (Journal of Educational and Psychological Sciences, 2022)
The study aimed at a detailed statement of the meanings of the terms psychological adjustment, manifestations and indicators of proper psychological adjustment, and a statement and the importance of psychological adjustment among school students, and the extent of the danger of neglecting the aspect of psychological adjustment among students, The researcher reached a set of results, including: Findings and recommendations: The lack of psychological compatibility and psychological comfort for the student may result in the student dropping out or deviating from the study, controlling the students’ emotions and building healthy relationships with individuals is an indicator of sound mental health and normal psychological compatibility, and the study advises to work on Strengthening the psychological state of students in the academic stages so that the student acquires a sound mental health that helps him to be creative and move towards self-realization, and to conduct further studies that study the impact of psychological adjustment on school students, especially the basic stages.